Leveraging Blockchain Technology to Strengthen Cybersecurity in Financial Transactions: A Comprehensive Analysis - David Arian Yusuf; Rio Wahyudin Anugrah; Maulana Arif Komara; Dwi Julianingsih; Emily Garcia (Pandawan Sejahtera Indonesia, 2024)
In the rapidly evolving digital landscape, financial transactions are increasingly vulnerable to cyber threats, necessitating advanced security measures beyond traditional methods like encryption and firewalls. This study explores the potential of blockchain technology as a robust framework for enhancing cybersecurity protocols in financial transactions. The primary objective is to assess how blockchain’s decentralized, transparent, and cryptographic features can mitigate risks such as fraud, unauthorized access, and data breaches. Employing a quantitative experimental design, the study simulated financial transactions on a blockchain platform and analyzed historical data on security breaches. The results indicate that blockchain technology significantly improves data security, with a 98% effectiveness rate in preventing and detecting breaches. However, challenges such as scalability, regulatory compliance, and high energy consumption were also identified. The findings suggest that while blockchain holds considerable promise for securing financial transactions, further innovation is necessary to address its limitations and fully leverage its capabilities in the financial sector.